Digital Game-Based Learning for Arabic Vocabulary: Assessing the Effectiveness of QuizWhizzer - Alfiatun Muniroh; Muhammad Afifudin Dimyathi; Muhammad Anwar (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2026)
Quizwhizzer is a web-based platform designed to create interactive quizzes in the form of games. This platform is very suitable for use in learning contexts, especially for teachers who want to make the class more relaxed, fun, and far from the impression of monotony packaged in the form of games, students become more enthusiastic to participate, without feeling forced to learn The purpose of this study is to see whether the use of Quizwhizzer learning media can have an effect on improving Arabic vocabulary mastery in class X students of MAN 1 Lamongan This study used a quantitative approach with an experimental research type, data collection techniques using tests in the form of pre-test and post-test scores. The sample used in this study was class X E with 36 students. The data in this study has been tested for normality and obtained results of 0.176; 0.000. Both significance values ​​are > 0.05, so it can be concluded that the data is normally distributed. The data in this study was also tested for homogeneity with a significance value of 0.268 which means the value is > 0.05. Thus, it can be concluded that the data is homogeneous, so a Paired sample t-test can be carried out. The results of the paired sample t-test obtained sig asymp 2 tailed (0.000 < 0.05), meaning that H0 is rejected and Ha is accepted with the conclusion that the use of quizwhizzer media is effective in improving students' mastery of Arabic vocabulary.